IMPACT OF MOTIVATION ON THE PERFORMANCE OF EMPLOYEES:A CASE STUDY OF BANKING INDUSTRY OF PAKISTAN (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The current research investigates the impact of motivation on the performance of employees: A Case study of banking industry of Pakistan. Data were collected from 200 respondents from Branch Managers to operation Managers five Banks UBL, HBL, ABL, Askari and Alfalah Bank limited. It was revealed that motivation has positive impact on the employee performance. It was further revealed that motivation is the only tool through you will satisfy your team. It was further revealed that most of the branch managers were not happy with long office hours from 9.am-9.pm. Motivation is the only factor that boost up their performance.